2022
DOI: 10.1038/s41533-022-00282-y
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with health status and exacerbations in COPD maintenance therapy with dry powder inhalers

Abstract: The study aimed to determine the associations of Peak Inspiratory Flow (PIF), inhalation technique and adherence with health status and exacerbations in participants with COPD using DPI maintenance therapy. This cross-sectional multi-country observational real-world study included COPD participants aged ≥40 years using a DPI for maintenance therapy. PIF was measured three times with the In-Check DIAL G16: (1) typical PIF at resistance of participant’s inhaler, (2) maximal PIF at resistance of participant’s inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(28 citation statements)
references
References 34 publications
0
20
0
Order By: Relevance
“…1091 abstracts were eliminated, leaving 55 full-text articles for review in detail. Among these articles, 36 did not contain information about associations between errors and outcomes or were review articles, resulting in a total of 19 publications that were included in this review5 11–28 (table 1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…1091 abstracts were eliminated, leaving 55 full-text articles for review in detail. Among these articles, 36 did not contain information about associations between errors and outcomes or were review articles, resulting in a total of 19 publications that were included in this review5 11–28 (table 1).…”
Section: Resultsmentioning
confidence: 99%
“…10 retrospective case–controlled studies, reported in 12 publications, compared the characteristics of patients who made and who did not make errors using their inhalers (table 1). 5 12 14 15 17 18 20 22 23 25 27 28 These included larger numbers of patients than the prospective studies. Three publications23 27 28 reported different outcomes from the same study (The PIFotal COPD study).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a cross-sectional multicountry observational real-world study by Kocks et al [6 ▪ ], participants aged ≥40 years with COPD using a DPI for maintenance therapy were included. PIF was measured three times with the In-Check DIAL G16: typical PIF at resistance of participant's inhaler, maximal PIF at resistance of participant's inhaler, maximal PIF at low resistance.…”
Section: Why Is Peak Inspiratory Flow Important?mentioning
confidence: 99%